2006
DOI: 10.1017/phn2005926
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, diet and gene–environment interactions in relation to body mass index and waist circumference: The Swedish Young Male Twins Study

Abstract: Objective: The aim of the present study was to examine the relationships between genetic susceptibility to obesity, physical activity (PA), dietary fibre, sugar and fat intakes and 4-year changes in body mass index (BMI) and attained waist circumference (WC) in a cohort of 287 monozygotic and 189 dizygotic young adult male twin pairs. Increased knowledge about interactions between genes and environment may provide insight into why some individuals are more prone to obesity than others. Design: Information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 21 publications
2
40
0
3
Order By: Relevance
“…The interaction of genes and physical activity may also evolve as subjects age, young men and women in their mid 20s probably being much more active than in their later years. Karnehed et al 20 found that twins genetically susceptible to obesity were more prone to large WC if they were sedentary than twins without such susceptibilityFa result in line with our findings. It was, however, unclear whether the high and low genetic risk groups differed in baseline BMI, WC and physical activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The interaction of genes and physical activity may also evolve as subjects age, young men and women in their mid 20s probably being much more active than in their later years. Karnehed et al 20 found that twins genetically susceptible to obesity were more prone to large WC if they were sedentary than twins without such susceptibilityFa result in line with our findings. It was, however, unclear whether the high and low genetic risk groups differed in baseline BMI, WC and physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…The researchers hypothesized that genes suppressing weight gain may be expressed only at high physical activity levels. Karnehed et al 20 used a model based on the co-twins' obesity status as an indicator of genetic risk to analyze gene-environment interaction. Among twins with genetic susceptibility to obesity, WC and weight gain were modified by physical activity level.…”
Section: Introductionmentioning
confidence: 99%
“…We have also conducted a collaborative study on the influences of physical activity, diet and geneenvironment interactions on 4-year changes in BMI and attained waist circumference (Karnehed et al, 2006). The results indicated that people with a sedentary lifestyle combined with genetic susceptibility to obesity had a greater 4-year increase in weight than those with no genetic susceptibility.…”
Section: Papers From the Swedish Young Male Twins Studymentioning
confidence: 99%
“…The long-term goal of this longitudinal twin study is to enable research on genetic and environmental influences on behavioral and biological risk factors for blood pressure, obesity, type 2 diabetes and cardiovascular diseases. The most recent research from this population-based twin cohort has explored relationships of fetal growth with body size and blood pressure in young adulthood (Johansson & Rasmussen, 2001;Johansson-Kark et al, 2002), genetic and environmental contributions to eating behavior (Tholin et al, 2005), and influences of physical activity, diet and gene-environment interactions on longitudinal changes in body mass index (BMI) and attained waist circumference (Karnehed et al, 2006). Other recent papers have focused on genetic factors in physical activity (Eriksson et al, 2006), and longitudinal changes in BMI and attained body fatness (Silventoinen et al, 2006).…”
mentioning
confidence: 99%
“…Using data from the Swedish Young Male Twins Register, Karnehed et al 1 found that low physical activity and low fibre intake were significantly associated with greater waist circumference in their sample. Moreover, they discovered an interaction between genetic susceptibility and physical activity: among twins with higher genetic susceptibility to greater waist circumference, low physical activity appeared to have a greater effect on attained waist circumference than it did among twins at low genetic risk.…”
mentioning
confidence: 99%